Recommendations on practice of conditioned pain modulation (CPM) testing - Yarnitsky, David; Treede, Rolf-Detlef (European journal of pain, 2015)
Protocols for testing conditioned pain modulation (CPM) vary between different labs/clinics. In order to promote research and clinical application of this tool, we summarize the recommendations of interested researchers consensus meeting regarding the practice of CPM and report of its results.